Neurones associated with saccade metrics in the monkey central mesencephalic reticular formation - Cromer, Jason A (Blackwell Science Inc, 2006)
Neurones in the central mesencephalic reticular formation (cMRF) begin to discharge prior to saccades. These long lead burst neurones interact with major oculomotor centres including the superior colliculus (SC) and the paramedian pontine reticular formation (PPRF). Three different functions have been proposed for neurones in the cMRF: (1) to carry eye velocity signals that provide efference copy information to the SC (feedback), (2) to provide duration signals from the omnipause neurones to the SC (feedback), or (3) to participate in the transformation from the spatial encoding of a target selection signal in the SC into the temporal pattern of discharge used to drive the excitatory burst neurones in the pons (feed-forward). According to each respective proposal, specific predictions about cMRF neuronal discharge have been formulated. Individual neurones should: (1) encode instantaneous eye velocity, (2) burst specifically in relation to saccade duration but not to other saccade metrics, or (3) have a spectrum of weak to strong correlations to saccade dynamics. To determine if cMRF neurones could subserve these multiple oculomotor roles, we examined neuronal activity in relation to a variety of saccade metrics including amplitude, velocity and duration. We found separate groups of cMRF neurones that have the characteristics predicted by each of the proposed models. We also identified a number of subgroups for which no specific model prediction had previously been established. We found that we could accurately predict the neuronal firing pattern during one type of saccade behaviour (visually guided) using the activity during an alternative behaviour with different saccade metrics (memory guided saccades). We suggest that this evidence of a close relationship of cMRF neuronal discharge to individual saccade metrics supports the hypothesis that the cMRF participates in multiple saccade control pathways carrying saccade amplitude, velocity and duration information within the brainstem.